FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DROP OUT AKSEPTOR KB DI KECAMATAN TEMBALANG KOTA SEMARANG - Ardiana Nur Aini; Atik Mawarni; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Acceptors drop out of family planning is acceptors that does not pass on an episode of the use of equipment / means of family planning in a period for various reasons, such as failure or experiencing side effects. Drop out of active family planning Semarang is large enough that in 2011 there were 16 055 acceptors, in 2012 amounted to 32 151 acceptors and in 2013 amounted to 34 849 acceptors. District Tembalang in Semarang is one of the areas with the highest drop out cases of 80 cases of drop out in 2013-2015. The purpose of this study to analyze factors related to the incidence of drop outs family planning acceptors in the district Tembalang Semarang. This type of research is explanatory research with Case Control Study research design and use a retrospective approach. The population consisted of 26 cases and the entire population of active family planning as a control population with a sampling technique using total population sampling ratio of 1: 1 was obtained 52 respondents consisting of 26 case samples and 26 control samples. Analysis of the data used univariate and bivariate analysis using chi square test with a significance level (α = 5%). Results of univariate analysis showed the largest percentage of low income (53.8%), the two categories of perception quality service is good and bad alike (50.0%), and side effects of contraception (86,5%). Results the bivariate analysis showed no relationship between income (p value = 0,404, OR = 1,867 and 95%CI = 0,202 – 1,887), perception of quality services of family planning (p value = 0,782, OR = 1,361 and 95%CI = 0,457 – 4,050) and the side effects of contraception (p value = 0,154 and 95%CI = 0,852 – 8,645) with incidence of drop out of family planning in Sub Tembalang Semarang. Suggested for more midwives to improve in providing contextual information about family planning in order to increase the number of family planning and family planning who drop out can be prevented and treated.